POLA KOMUNIKASI INTERPERSONAL PENGURUS ASRAMA DALAM PEMBENTUKAN KARAKTER SANTRI PUTRA MADRASAH ALIYAH MA’HAD AL-ZAYTUN - Afiandani, Difo; Bakhrudin, Elang; Peranginangin, Henri (Cahaya Ilmu Bangsa Institute, 2024)
The development of the times can lead a santri to a better direction, or even plunge into the bad if it can not carry themselves carefully. Interpersonal communication patterns have a big role in instilling and shaping the character of students. This study aims to determine the pattern of interpersonal communication in forming the character of the students of madrasah aliyah Ma'had Al-Zaytun by finding out the supporting factors and factors inhibiting the success of character formation. From the results of the study it was found that the pattern of interpersonal communication dormitory administrators in the formation of the character of the students of madrasah aliyah Ma'had Al-Zaytun using linear patterns and wheel patterns. The supporting factors are openness and personality of the dormitory management. Inhibiting factors are negative perception and lack of openness of students to the dormitory management, diverse cultural cultures, and feelings or emotional. Keywords: Pattern, Interpersonal Communication, Character Building, Students, Dormitory.